Effective Stiffness and Damping Analysis of Steel Damper to Lateral Cyclic Loading - Bastian A. Ampangallo; Herman Parung; Rita Irmawaty; Arwin Amiruddin (Civil Engineering Journal, 2024)
Steel dampers are components used in building structures to reduce vibration and energy generated by dynamic loads such as earthquakes. Several factors affect the effectiveness of steel dampers in reducing energy, including the cross-sectional area, mass distribution, cross-sectional geometry, and material stiffness. The cross-sectional geometry or shape of the steel damper can affect how energy is absorbed and dissipated in the structural system. Cross sections with different geometric variations can have different mechanical responses to dynamic loads. This study aims to analyze which type of steel damper is effective in terms of stiffness and damping capacity against lateral cyclic loads. The steel damper cross-sectional variations used are slit steel dampers (SSDs), tapered steel dampers (TSDs), and oval steel dampers (OSDs). Cyclic testing of the dampers used displacement control with the same target deviation for all three damper types. The results showed that the stress and strain distributions of the oval steel damper were more even than those of the other two models. The variations in the energy dissipation capacities of the three cross-section variations are relatively the same. However, the slit steel damper type has the best stiffness compared to the other two types. This research is ultimately expected to influence the science of the structure of a building in preventing and anticipating earthquakes or other disasters. Doi: 10.28991/CEJ-2024-010-07-017 Full Text: PDF